Influence of Ge4+ substitution for Zr4+ on the microwave dielectric properties of Mg(Zr1-xGex)Nb2O8 (0 ≤x ≤ 0.4) ceramics. Issue 17 (1st December 2018) - Xiao, Mi; He, Susu; Lou, Jie; Zhang, Ping
Abstract: Dense Mg(Zr1-x Gex )Nb2 O8 (x = 0, 0.1, 0.2, 0.3, 0.4) ceramics were successfully synthesized through traditional solid state reaction route. The relations between microstructure and microwave dielectric properties were studied. The formation of single MgZrNb2 O8 phase with the monoclinic wolframite structure was verified by XRD patterns. Experimental dielectric constant was found to be closely related to bond polarizability, and theoretical dielectric constant calculated based on P-V-L theory shows the same tendency with the experimental dielectric constant when the substitution amount of Ge 4+ changes. The increase in Q × f and | τ f | were mainly attributed to the increase in packing fraction and the Nb-site bond valence, respectively. Excellent dielectric properties were obtained for Mg(Zr1-x Gex )Nb2 O8 (x = 0.2) ceramic sintered at 1300 °C for 4 h: ε r = 24.26, Q × f = 80, 492.8 GHz, τ f = -51.95 ppm/°C.